Modified artificial graphite as well as preparation method and application thereof
Through the preparation method of modified artificial graphite, combined with granulation, graphitization and organic carboxylic acid treatment, a conductive carbon cladding layer and rich pore structure are formed, which solves the problems of taking into account both magnification and cycling performance in the prior art, and realizes the Highly efficient electrochemical performance and low cost process.
Patent Information
- Application Number
- CN202411374035.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to take into account both high rate performance and high cycle performance in graphite negative electrode materials, and the process cost is high and the process is difficult to achieve stable SEI film formation.
Through the preparation method of modified artificial graphite, including granulation, graphitization, carbonization and organic carboxylic acid treatment, a conductive carbon coating layer and rich pore structures and functional groups are formed, thereby improving the circulation and rate performance of the material.
It significantly improves the circulation performance and rate performance of modified artificial graphite, ensures the long circulation performance and fast charging capability of the battery cell, and reduces process costs and safety risks.
Smart Images

Figure BDA0005068268550000081 
Figure BDA0005068268550000091 
Figure BDA0005068268550000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of secondary battery materials, and in particular to a modified artificial graphite and a preparation method and application thereof. Background Art
[0002] In recent years, the new energy industry, including the new energy vehicle industry, has developed rapidly. Therefore, the demand for power EV batteries has also increased. Further improving the charge and discharge rate of the battery has become a new market demand. Therefore, it is urgent to find a graphite negative electrode material with high rate and high cycle performance.
[0003] In order to improve the rate performance of graphite negative electrode materials, related technologies often try to reduce the particle size of the material, or dope it. In order to improve the cycle of graphite negative electrode materials, related technologies often use coating or improving the particle size and morphology regularity of the material.
[0004] However, the above method has disadvantages such as high processing cost and high process difficulty of some processes on the one hand, and it is usually difficult to take into account both rate performance and cycle performance on the other hand. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a method for preparing modified artificial graphite, which can effectively enrich its pore structure and form more -COOH or -C=O functional groups on its surface; thereby forming a stable SEI film during use. Overall, the cycle performance and rate performance of the modified artificial graphite can be improved.
[0006] The invention also provides modified artificial graphite prepared by the preparation method.
[0007] The invention also provides application of the modified artificial graphite.
[0008] According to an embodiment of the first aspect of the present invention, a method for preparing modified artificial graphite is provided, the preparation method comprising the following steps:
[0009] S1. granulating the needle-shaped green coke and the binder to obtain a precursor;
[0010] S2. graphitizing the precursor;
[0011] S3. The product obtained in step S2 is mixed with a liquid resin and then carbonized to obtain a semi-finished graphite product; the particle size concentration of the semi-finished graphite product is b%; and b = (Dv95-Dv5) / Dv50, 1≤b≤2;
[0012] S4. Treating the graphite semi-finished product with an organic carboxylic acid; the mass percentage of the organic carboxylic acid in the graphite semi-finished product is c%, and 6≤c≤10.
[0013] The mechanism of the preparation method is as follows:
[0014] In step S1, granulation and shaping are performed to obtain a precursor that basically meets the parameters required by step S3;
[0015] In step S2, a graphitized product with high crystallinity is obtained;
[0016] In step S3, the conductive carbon coating layer is formed by coating with a liquid phase resin as a carbon source;
[0017] In step S4, during the treatment with organic carboxylic acid, on the one hand, it has the function of forming pores, and on the other hand, it can graft oxygen-containing groups such as carboxyl and aldehyde groups onto the graphite semi-finished product.
[0018] The preparation method according to the embodiment of the present invention has at least the following beneficial effects:
[0019] In the preparation method provided by the present invention, the graphitized semi-finished product in step S3 partially inherits the morphology of the precursor obtained in step S1. Therefore, through the granulation in step S1, a graphite semi-finished product with a specific particle size distribution is obtained, and the more uniform the particle size of the graphite negative electrode material is, the better its cycle performance is, because the granulation in step S1 and the screening of the particle size in step S3 provide a guarantee for obtaining modified artificial graphite with excellent cycle performance in the later stage.
[0020] The rate performance (fast charging performance) of graphite negative electrode materials is affected to a certain extent by their electronic conductivity. In the preparation method provided by the present invention, carbon coating is performed in step S3, thereby improving the rate performance of the obtained modified artificial graphite.
[0021] In the preparation method provided by the present invention, in step S4, more active sites and unique functional groups are generated on the surface of the modified artificial graphite, among which the carboxyl functional group will generate stable inorganic substances when the battery cell is charged and discharged, which is conducive to the formation of a more stable SEI and ensures the long cycle performance of the battery cell. At the same time, the generated active sites also have the ability to quickly adsorb lithium ions, that is, the modified artificial graphite provided by the present invention has a higher gram-to-gram capacity and better fast charging capability.
[0022] In conventional techniques, the acid used for pore formation is mostly an inorganic strong acid, or is carried out with the assistance of a strong oxidant. The present invention creatively uses an organic carboxylic acid and does not require a strong oxidant. Therefore, the preparation process is safer and the reagent cost is lower. In addition, the organic carboxylic acid is used to form pores while also having a grafting effect.
[0023] In summary, in the preparation method provided by the present invention, the cycle performance, rate performance and capacity are significantly improved through the synergistic effect between the steps and parameters; and the preparation process is gentler, lower in cost and better in effect.
[0024] According to some embodiments of the present invention, in step S1, the sulfur content of the needle coke is a%, and 0.5≤a≤2. The specific value of a can be about 0.8, 1.0, 1.2, 1.5 or about 1.8.
[0025] According to some embodiments of the present invention, in step S1, the particle size of the needle-shaped green coke is 7 to 9 μm. If the particle size of the directly obtained needle-shaped green coke raw material is not within this range, step S1 also includes crushing, shaping and screening the needle-shaped green coke before the granulation. The crushing method includes grinding. Unless otherwise specified, the particle size mentioned in the present invention refers to the median particle size, i.e. D50; further, for any solid powder, the distribution of particle size is close to a normal distribution.
[0026] According to some embodiments of the present invention, in step S1, the binder includes solid phase asphalt.
[0027] According to some embodiments of the present invention, in step S1, the softening point of the binder is 80-250°C, for example, about 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 230°C or about 240°C.
[0028] According to some embodiments of the present invention, in step S1, the coking value of the binder is 20% to 70%, for example, about 30%, 40%, 50% or about 60%.
[0029] According to some embodiments of the present invention, in step S1, the mass ratio of the needle-shaped green coke to the binder is 100:3-20, for example, about 100:5, 100:10 or about 100:15.
[0030] According to some embodiments of the present invention, in step S1, the granulation method includes heating and stirring the mixture of the needle-shaped green coke and the binder in an inert atmosphere, wherein the heating and stirring temperature is 300 to 500° C. and the heating and stirring time is 1 to 5 hours.
[0031] According to some embodiments of the present invention, in step S1, the particle size of the precursor is 8-12 μm.
[0032] According to some embodiments of the present invention, in step S2, the temperature of the graphitization treatment is 2800-3000°C, for example, about 2850°C, 2900°C or about 2950°C.
[0033] According to some embodiments of the present invention, in step S2, the duration of the graphitization treatment is 2 to 10 hours, for example, about 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours or about 9 hours.
[0034] According to some embodiments of the present invention, in step S3, the liquid phase resin includes at least one of phenolic resin, epoxy resin and urea-formaldehyde resin.
[0035] According to some embodiments of the present invention, in step S3, the solid content of the liquid phase resin is 1-5%, for example, about 2%, 3% or about 4%.
[0036] According to some embodiments of the present invention, in step S3, the mass ratio of the product obtained in step S2 to the liquid phase resin is 8 to 12:1, for example, about 9:1, 10:1 or about 11:1.
[0037] According to some embodiments of the present invention, in step S3, the mixing is performed in a fusion machine.
[0038] According to some embodiments of the present invention, in step S3, the mixing stirring speed is 400 to 1200 rpm. For example, it can be about 500 rpm, 800 rpm or about 1000 rpm. The greater the stirring speed, the smaller the b value, that is, the particle size of the graphite semi-finished product is more concentrated, which provides convenience for further adjustment of the b value in the subsequent process.
[0039] According to some embodiments of the present invention, in step S3, the mixing time is 5 to 30 minutes.
[0040] According to some embodiments of the present invention, in step S3, the carbonization temperature is 1000-1500°C, for example, about 1100°C, 1200°C, 1300°C or about 1400°C.
[0041] According to some embodiments of the present invention, in step S3, the carbonization time is 1 to 6 hours, for example, about 2 hours, 3 hours, 4 hours or about 5 hours.
[0042] According to some embodiments of the present invention, in step S3, the carbonization is performed in an inert gas.
[0043] According to some embodiments of the present invention, step S3 further includes, after the carbonization, performing particle size classification on the obtained carbonized product. Specifically, it can be performed using relevant equipment such as an airflow classifier. In actual production, a suitable classification equipment can be selected according to demand and experimental conditions, and the present invention does not impose strict restrictions. In this way, accurate regulation of the b value can be achieved.
[0044] According to some embodiments of the present invention, in step S3, the specific value of b may be approximately 1.2, 1.5 or approximately 1.8.
[0045] According to some embodiments of the present invention, in step S3, the Dv5 of the graphite semi-finished product is 3-6.8 μm, for example, about 3.5 μm, 4 μm, 5 μm, 6 μm or about 6.5 μm.
[0046] According to some embodiments of the present invention, in step S3, the Dv50 of the graphite semi-finished product is 10-13 μm, for example, about 11 μm or about 12 μm.
[0047] According to some embodiments of the present invention, in step S3, the Dv95 of the graphite semi-finished product is 18-23 μm, for example, about 19 μm, 20 μm, 21 μm or about 22 μm.
[0048] According to some embodiments of the present invention, in step S4, the organic carboxylic acid includes at least one of formic acid, acetic acid, propionic acid and butyric acid.
[0049] According to some embodiments of the present invention, in step S4, the treatment temperature is 40-80°C, for example, about 50°C, 60°C or about 70°C.
[0050] According to some embodiments of the present invention, in step S4, the duration of the processing is 100 to 150 minutes, for example, about 110 minutes, 120 minutes, 130 minutes or about 140 minutes.
[0051] According to some embodiments of the present invention, in step S4, the value of c may specifically be approximately 7, 8 or approximately 9.
[0052] According to some embodiments of the present invention, 0.15<(a+b) / c<0.7. Within this range, the surface pore size of the obtained modified artificial graphite and the number of surface functional groups can be regulated by selecting the amount of needle-shaped raw coke, semi-finished graphite and organic carboxylic acid, thereby improving the fast charging performance of the obtained modified artificial graphite and further ensuring the stability of the cycle.
[0053] According to some embodiments of the present invention, the specific value of (a+b) / c is approximately 0.18, 0.2, 0.23, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or approximately 0.6.
[0054] According to some embodiments of the present invention, step S4 further includes washing and drying in sequence after the treatment, wherein the number of washings is ≥ 3 times.
[0055] According to an embodiment of the second aspect of the present invention, there is provided a modified artificial graphite obtained by the preparation method.
[0056] Since the artificial graphite adopts all the technical solutions of the preparation method of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment, that is, the modified artificial graphite has good rate performance, cycle performance and capacity.
[0057] According to some embodiments of the present invention, the BET of the modified artificial graphite is 1.5 to 3.5 m 2 / g. For example, it can be about 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.0m 2 / g, 2.1m 2 / g, 2.2m 2 / g, 2.3m 2 / g, 2.4m 2 / g, 2.5m 2 / g, 3.0m 2 / g, 3.1m 2 / g, 3.2m 2 / g or about 3.4m 2 / g.
[0058] According to some embodiments of the present invention, oxygen-containing groups are grafted onto the modified artificial graphite, and the oxygen-containing groups include at least one of carboxyl groups and aldehyde groups.
[0059] According to some embodiments of the present invention, the modified artificial graphite has a core-shell structure, wherein the shell layer is a conductive carbon layer.
[0060] According to some embodiments of the present invention, the gram specific capacity of the modified artificial graphite at a current density of 0.2A / g is ≥330mAh / g, for example, about 360mAh / g, 355mAh / g, 350mAh / g, 345mAh / g, 340mAh / g, or 335mAh / g.
[0061] According to some embodiments of the present invention, the modified artificial graphite has a capacity retention rate of ≥64% for 600 weeks at a current density of 0.2 A / g, for example, about 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84% or about 85%.
[0062] According to some embodiments of the present invention, the gram specific capacity of the modified artificial graphite at a current density of 0.5A / g is ≥285mAh / g, for example, about 305mAh / g, 300mAh / g, 295mAh / g or about 290mAh / g.
[0063] According to some embodiments of the present invention, the gram specific capacity of the modified artificial graphite at a current density of 1A / g is ≥240mAh / g, for example, about 270mAh / g, 260mAh / g, 260mAh / g, 255mAh / g, 250mAh / g or about 245mAh / g.
[0064] According to some embodiments of the present invention, the gram specific capacity of the modified artificial graphite at a current density of 2A / g is ≥189mAh / g, for example, about 215mAh / g, 210mAh / g, 205mAh / g, 200mAh / g, 195mAh / g or about 190mAh / g.
[0065] According to an embodiment of the third aspect of the present invention, a negative electrode slurry is provided, and the raw material for preparing the negative electrode slurry includes the modified artificial graphite.
[0066] Since the negative electrode slurry adopts all the technical solutions of the modified artificial graphite in the above embodiment, it at least has all the beneficial effects brought by the technical solutions in the above embodiment.
[0067] According to some embodiments of the present invention, the pH of the negative electrode slurry is 5 to 7. For example, it can be about 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8 or about 6.9.
[0068] According to some embodiments of the present invention, the raw materials for preparing the negative electrode slurry further include a conductive agent, a binder and water.
[0069] According to some embodiments of the present invention, the modified artificial graphite accounts for 95-98.5% by mass of the solids in the negative electrode slurry, for example, about 96%, 96.5%, 97%, 97.5% or about 98%.
[0070] According to some embodiments of the present invention, the solid content of the negative electrode slurry is 45-50%, for example, about 48%.
[0071] According to an embodiment of the fourth aspect of the present invention, a lithium-ion battery is provided, wherein the raw materials for preparing the lithium-ion battery include the modified artificial graphite, or include the negative electrode slurry.
[0072] Since the lithium-ion battery adopts all the technical solutions of the modified artificial graphite or negative electrode slurry of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments.
[0073] According to some embodiments of the present invention, the lithium-ion battery includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte that soaks the above components;
[0074] The negative electrode comprises a negative electrode current collector and a negative electrode coating disposed on the surface of the negative electrode current collector;
[0075] The raw material for preparing the negative electrode coating includes the modified artificial graphite or the negative electrode slurry.
[0076] According to some embodiments of the present invention, the positive electrode includes a positive electrode current collector and a positive electrode coating disposed on a surface of the positive electrode current collector.
[0077] According to some embodiments of the present invention, the raw material for preparing the positive electrode coating includes a positive electrode active material.
[0078] According to some embodiments of the present invention, the positive electrode active material includes at least one of a polyanion material, a layered material, and a spinel material.
[0079] The polyanion material includes at least one of lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.
[0080] The general formula of the layered material is LiMO2, wherein M includes at least one of nickel, cobalt and manganese, for example, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide or lithium nickel cobalt manganese oxide.
[0081] In the layered material, M also includes a doping element; the doping element includes at least one of aluminum, zirconium, magnesium, titanium, boron, and fluorine.
[0082] The spinel material includes lithium manganate (spinel phase).
[0083] According to some embodiments of the present invention, the lithium-ion battery includes at least one of a button battery, a soft-pack battery, a square-shell battery, and a cylindrical battery.
[0084] According to an embodiment of the fifth aspect of the present invention, there is provided an application of the lithium-ion battery in the field of power batteries, the field of energy storage batteries and 3C products.
[0085] Since the application adopts all the technical solutions of the lithium-ion battery of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment.
[0086] If not otherwise specified, the inert atmosphere in the present invention includes at least one of nitrogen and argon.
[0087] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.
[0088] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values 2 and 3.
[0089] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0090] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0091] Figure 1 is a SEM image of the modified artificial graphite obtained in Example 2 of the present invention;
[0092] Figure 2 is a SEM image of the modified artificial graphite obtained in Comparative Example 1 of the present invention;
[0093] Figure 3 This is a SEM image of the modified artificial graphite obtained in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0094] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0095] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0096] Example 1
[0097] In this example, a modified artificial graphite was prepared, and the specific steps were as follows:
[0098] S1. Grind, crush, shape and sieve needle-shaped raw coke with a sulfur content of 0.5% (a = 0.5) to obtain single particles with a D50 particle size of 8 μm;
[0099] The single particles and the binder asphalt are mixed evenly in a mass ratio of 100:10 and then transferred to a reactor. In an inert atmosphere of nitrogen or argon, the particles are granulated by stirring and heating, and a precursor with a D50 particle size of 10 μm is obtained after screening.
[0100] The softening point of the asphalt is 120°C and the coking value is 50%; the temperature of the stirring and heating granulation is 400°C and the duration is 2 hours.
[0101] S2. The precursor obtained in step S1 is transferred to a graphitization furnace for high-temperature graphitization treatment to obtain an intermediate product with high crystallinity; wherein the temperature of the high-temperature graphitization treatment is 2900°C, the duration is 6 hours, and the atmosphere is a nitrogen inert atmosphere.
[0102] S3. The intermediate product obtained in step S2 and the liquid resin (phenolic resin with a solid content of 3%) are transferred to a fusion machine at a mass ratio of 10:1 for mechanical homogeneous mixing (the speed of the fusion machine is 800 rpm and the mixing time is 20 min), and then transferred to a carbonization furnace for carbonization treatment in an inert atmosphere to obtain a carbon-coated graphite semi-finished product; the particle size concentration of the graphite semi-finished product is controlled to be b% in a grading device; and b = (Dv95-Dv5) / Dv50, Dv95 = 18 μm, Dv50 = 13 μm, Dv5 = 5 μm, and the specific value of b is shown in Table 1; wherein,
[0103] The temperature of carbonization treatment is 1200℃ and the duration is 3h.
[0104] S4. The graphite semi-finished product obtained in step S3 is mixed with formic acid in a weight ratio of 100:6 (c=6), and heated at 40° C. for 120 min to obtain an acid-treated graphite semi-finished product. The acid-treated graphite semi-finished product is washed three times with deionized water and then placed in an oven for drying to obtain modified artificial graphite.
[0105] Examples 2-13 and Comparative Examples 1-3 respectively prepared a modified artificial graphite, which differed from Example 1 in that some parameters were different. The specific parameter differences are shown in Table 1.
[0106] That is, the only difference between Example 2-3 and Example 1 is that the acid treatment temperature of step S4 is different, the acid treatment temperature of Example 1 is 40°C, the acid treatment temperature of Example 2 is 60°C, and the acid treatment temperature of Example 3 is 80°C.
[0107] The only difference between Example 4-6 and Example 2 is that the sulfur content of the needle coke used in step S1 is different. The sulfur content of the needle coke in Example 2 is 0.5% (a=0.5), the sulfur content of the needle coke in Example 4 is 1.0% (a=1), the sulfur content of the needle coke in Example 5 is 1.5% (a=1.5), and the sulfur content of the needle coke in Example 6 is 2.0% (a=2).
[0108] The difference between Examples 7-8 and Comparative Example 2 and Example 2 is that the particle size concentration of the graphite semi-finished product prepared in step S3 is different. The particle size concentration of the graphite semi-finished product prepared in step S3 of Example 2 is 1% (b=1). The particle size concentration of the graphite semi-finished product prepared in step S3 of Example 7 is 1.5% (b=1.5). The particle size of the material is controlled by the classifier of the equipment so that the Dv95 of the graphite semi-finished product is 20μm, Dv50=10.5μm, Dv5=4μm, and b=(Dv95-Dv5) / Dv50. The particle size concentration of the graphite semi-finished product prepared in step S3 of Example 8 is 2% (b=2). The particle size of the material is controlled by the classifier of the equipment so that the Dv95 of the graphite semi-finished product is 23μm, Dv50=10μm, Dv5=3μm, and b=(Dv95-Dv5) / Dv50. The particle size concentration of the graphite semi-finished product prepared in step S3 of comparative example 2 is 0.8% (b=0.8). The particle size of the material is controlled by the classifier of the equipment so that Dv95=17μm, Dv50=13μm, Dv5=6.5μm, and b=(Dv95-Dv5) / Dv50 of the graphite semi-finished product.
[0109] The only difference between Example 9-10 and Example 2 is that the acid type used in the acid treatment in step S4 is different. The organic carboxylic acid used in Example 2 is formic acid, the organic carboxylic acid used in Example 9 is acetic acid, and the organic carboxylic acid used in Example 10 is propionic acid.
[0110] The difference between Examples 11-12 and Comparative Example 3 and Example 2 is that the organic carboxylic acid content added in step S4 acid treatment is different. Example 2 adds the graphite semi-finished product to formic acid at a weight ratio of 100:6 (c=6), Example 11 adds the graphite semi-finished product to formic acid at a weight ratio of 100:8 (c=8), and Example 12 adds the graphite semi-finished product to formic acid at a weight ratio of 100:10 (c=10). Comparative Example 3 adds the graphite semi-finished product to formic acid at a weight ratio of 100:15 (c=15).
[0111] The only difference between Example 13 and Example 8 is that the sulfur content of the needle coke used in step S1 is different. The sulfur content of the needle coke in Example 8 is 0.5% (a=0.5), and the sulfur content of the needle coke in Example 13 is 2.2% (a=2.2).
[0112] The difference between Comparative Example 1 and Example 2 is that step S4 is not performed in Comparative Example 1.
[0113] Table 1 Comparison of the differences between the embodiments and the comparative examples
[0114]
[0115]
[0116] Application Examples
[0117] This example provides a negative electrode slurry, and uses the negative electrode slurry as a raw material to prepare a negative electrode sheet:
[0118] Specifically, the modified artificial graphite obtained in the embodiment and the comparative example, the conductive agent SP, the binder (CMC: SBR = 1.1: 0.7) and water were mixed in a mass ratio of 97.7: 0.5: 1.8 to obtain a negative electrode slurry with a solid content of 45% to 50% (the set value is 48%, due to errors, it may fluctuate between 45% and 50% in actual production, which has little effect on the test results). The pH of the negative electrode slurry was tested and integrated as shown in Table 2.
[0119] The preparation method of the negative electrode sheet is as follows: apply the negative electrode slurry obtained in Application Example 1 on the current collector copper foil, dry it at 85°C, then trim, cut and strip it; and dry it again at 85°C under vacuum for 12 hours to obtain the negative electrode sheet.
[0120] Test Case
[0121] In the first aspect of this example, SEM was used to test the morphology of the modified artificial graphite obtained in the example and the comparative example. The results showed that the roughness of the modified artificial graphite after acid washing was slightly improved, and the roughness increased with the increase of the amount of acid used. However, since the pore structure on the modified artificial graphite is relatively small, the resolution of the SEM image cannot support the display. Specifically, the morphology of the modified artificial graphite obtained in Example 1 is as follows: Figure 1 As shown, the morphology of the modified artificial graphite obtained in Comparative Example 1 is as follows Figure 2 As shown, the morphology of the modified artificial graphite obtained in Comparative Example 3 is as follows Figure 3 shown.
[0122] In the second aspect of this example, the pore structure of the modified artificial graphite obtained in the embodiment and the comparative example was tested by BET. The results showed that the acid washing treatment in step S4 significantly improved the pore structure on the modified artificial graphite obtained, and improved the BET value, and the improvement of the BET value increased with the amount of acid used; this also corroborated the SEM test in the first aspect of this example. The specific results are shown in Table 2.
[0123] The third aspect of this example tests the pH of the negative electrode slurry obtained in the application example, specifically using a pH meter for testing. In the preparation method provided by the present invention, multiple water washings are performed after pickling, so the change in the pH value of the negative electrode slurry cannot come from free carboxylic acids, but from carboxyl groups grafted on the modified artificial graphite. The pH test results show that pickling can effectively reduce the pH of the negative electrode slurry. This shows that the preparation method provided by the present invention has indeed successfully grafted oxygen-containing groups such as carboxyl groups on the obtained modified artificial graphite. The test results are integrated as shown in Table 2.
[0124] The fourth aspect of this example tests the electrochemical performance of the negative electrode sheet obtained in the application example. Specifically, the negative electrode sheet obtained in the application example, the counter electrode lithium sheet, the separator, and the electrolyte are assembled into a button-type lithium-ion half-cell in a glove box filled with argon gas, and then the following electrochemical properties are tested:
[0125] Cycle performance test: ① Place the prepared button cell in a constant temperature box at (25±2)℃; ② Let stand for 10min; ③ Discharge to 0.005V with a current of 1A / g (the duration of this stage corresponds to the duration of the first stage charge in Table 2), and then discharge to 0.005V with a current of 0.2A / g; ④ Let stand for 5min; ⑤ Charge to 2V with a current of 0.2A / g; ⑥ Cycle the above steps ② to ⑤ 600 times; Record the discharge capacity of the battery after 2 cycles, recorded as D2, and the discharge capacity after each cycle as Dn, the capacity retention rate = Dn / D2, that is, the capacity retention rate of 600cls is D600 / D2;
[0126] Rate performance test:
[0127] Initialization module: ① Place the prepared button cell in a constant temperature box at (25±2)℃; ② Let stand for 10 minutes; ③ Discharge to 0.005V at a current of 0.2A / g; ④ Let stand for 5 minutes; ⑤ Charge to 2V at a current of 0.2A / g; ⑥ Let stand for 5 minutes;
[0128] Rate discharge module:
[0129] ①Discharge to 0.005V with a current of 0.1A / g; ②Stand for 5 minutes; Step description: record the specific capacity of discharge at this time, recorded as C1; ③Charge to 2V with a current of 0.2A / g; ④Stand for 5 minutes; ⑤Discharge to 0.005V with a current of 0.2A / g; ⑥Stand for 5 minutes; Step description: record the specific capacity of discharge at this time, recorded as C2; ⑦Charge to 2V with a current of 0.2A / g; ⑧Stand for 5 minutes; ⑨Discharge to 0.005V with a current of 0.5A / g; ⑩Stand for 5 minutes; Step description: record the specific capacity of discharge at this time, recorded as C3; Charge to 2V at a current of 0.2A / g; Let stand for 5 minutes; Discharge to 0.005V at a current of 1.0A / g; Let stand for 5 minutes; Step description: record the discharge capacity at this time, recorded as C4; Charge to 2V at a current of 0.2A / g; Discharge to 0.005V at a current of 2.0A / g; Let stand for 5 minutes; Step description: record the discharge capacity at this time, recorded as C5; Charge to 2V at a current of 0.2A / g.
[0130] The above cycle and rate performance results are summarized in Table 2.
[0131] Table 2 Test results of embodiments and comparative examples
[0132]
[0133]
[0134] In Table 2, the duration of the first stage of 50-cycle charging represents the polarization capacity of the negative electrode. The longer the time, the better the kinetic performance and the smaller the polarization.
[0135] The electrochemical performance test results of Examples 2, 4 to 6, and the comparison of the results of Examples 8 and 13 show that in the needle-shaped green coke, the less the content of the main impurity component S, the more perfect the crystal structure, and the higher the specific capacity of the obtained modified artificial graphite. Furthermore, the comparison of the results of Examples 8 and 13 also shows that the limited range of the (a+b) / c value has a certain influence on the performance of the modified artificial graphite obtained by the present invention.
[0136] The electrochemical performance test results of Examples 1 to 3 show that with the increase of the acid treatment temperature, the electrochemical performance of the modified artificial graphite obtained shows a trend of first increasing and then decreasing. This is because the organic carboxylic acid will slightly decompose with the increase of temperature, and the pore-forming performance and the content of carboxyl groups on the modified artificial graphite obtained will both decrease. At the same time, with the increase of temperature, the intensity of the main reaction in the pickling process will also increase, which will improve the pore-forming performance and / or the carboxyl content on the surface of the modified artificial graphite to a certain extent. The above trend appears after the combination of these two factors.
[0137] The electrochemical performance test results of Examples 2, 11-12, Comparative Examples 1 and 3 show that different proportions of formic acid will have a significant impact on the performance of the battery cell during the pickling process. This is because different proportions of formic acid will introduce different carboxyl functional groups. The trace amount of carboxyl functional groups can form a dense inorganic layer during negative electrode film formation, thereby improving the rate performance and cycle performance of the material, which is consistent with the 50cls discharge time in the cycle.
[0138] The electrochemical performance results of Examples 2, 7, 8 and Comparative Example 2 show that the particle size concentration (b value) of the graphite semi-finished product will also affect the performance of the battery cell. If the distribution is too narrow, the modified artificial graphite is not effectively etched by the organic carboxylic acid, fewer carboxyl functional groups are introduced, and the material is not significantly improved; if the distribution is slightly wide, too many carboxyl functional groups are introduced, which is not conducive to the rate and cycle performance of the negative electrode material.
[0139] From the comparison of the results of Examples 1, 9 to 10, it can be seen that when equal amounts of different types of organic carboxylic acids are used, the total amount of carboxyl groups is different and the activity of the carboxyl groups is also different, which has a certain influence on the electrochemical properties and physicochemical properties of the modified artificial graphite obtained. Specifically, within the range provided by the present invention, the more carboxyl content, the stronger the carboxyl activity, and the better the performance of the modified artificial graphite obtained.
[0140] In summary, the modified artificial graphite negative electrode material provided by the present invention, due to the introduction of oxygen-containing functional groups such as carboxyl groups, can form a dense SEI film during negative electrode film formation to ensure the cycle performance of the battery cell. At the same time, the present invention brings additional lithium storage channels, which can improve the kinetic properties of the negative electrode material and meet the growing demand for fast charging. In addition, the present invention only needs to add a simple process step to the conventional artificial graphite process, and the possibility of industrialization is higher. It is precisely because of the above-mentioned excellent effects that lithium-ion batteries including modified artificial graphite obtained by the present invention are expected to be widely used in the fields of power batteries, energy storage batteries and 3C products.
[0141] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing modified artificial graphite, characterized in that: The preparation method comprises the following steps: S1. granulating the needle-shaped green coke and the binder to obtain a precursor; S2. graphitizing the precursor; S3. The product obtained in step S2 is mixed with a liquid resin and then carbonized to obtain a semi-finished graphite product; the particle size concentration of the semi-finished graphite product is b%; and b = (Dv95-Dv5) / Dv50, 1≤b≤2; S4. Treating the graphite semi-finished product with an organic carboxylic acid; the mass percentage of the organic carboxylic acid in the graphite semi-finished product is c%, and 6≤c≤10.
2. The preparation method according to claim 1, characterized in that: In step S1, the sulfur content of the needle coke is a%, and 0.5≤a≤2; and 0.15<(a+b) / c<0.
7.
3. The preparation method according to claim 1, characterized in that: In step S1, the particle size of the needle-shaped coke is 7-9 μm; and / or, in step S1, the particle size of the precursor is 8-12 μm.
4. The preparation method according to claim 1, characterized in that: In step S4, the organic carboxylic acid includes at least one of formic acid, acetic acid, propionic acid and butyric acid.
5. The preparation method according to claim 1, characterized in that: In step S4, the treatment temperature is 40-80°C; and / or, in step S4, the treatment duration is 100-150 minutes.
6. A modified artificial graphite obtained by the preparation method according to any one of claims 1 to 5.
7. The modified artificial graphite according to claim 6, characterized in that: The BET of the modified artificial graphite is 1.5 to 3.5 m 2 / g.
8. A negative electrode slurry, characterized in that: The raw material for preparing the negative electrode slurry includes the modified artificial graphite as claimed in claim 6 or 7; and / or the pH of the negative electrode slurry is 5-7.
9. A lithium ion battery, characterized in that: The raw material for preparing the lithium-ion battery includes the modified artificial graphite as described in claim 6 or 7, or includes the negative electrode slurry as described in claim 8.
10. Application of the lithium-ion battery according to claim 9 in the fields of power batteries, energy storage batteries and 3C products.